Growth of large langatate (La3Ta0.5Ga5.5O14, LTG) crystals with high electrical resistivity. (August 2022) - Wang, Shuai; Ji, Cheng; Dai, Peng; Guo, Guobiao; Shen, Liming; Bao, Ningzhong
Highlights: A large LTG crystal was successfully grown with the Czochralski method in air. The as-grown LTG crystal possesses great qualities of crystalline perfection, piezoelectric performance and thermal properties. The electrical resistivity of LTG was improved to 2.45 *10 8 Ωcm at 500°C after being annealed in Ar at 1100°C for 10 h. The obtained high-quality large LGT crystal can be used in the field of high-temperature piezoelectric sensors. Abstract: Large, 60 mm in diameter langatate (La3 Ta0.5 Ga5.5 O14, LTG) crystals were grown with the Czochralski method in air. The full width at half maximum (FWHM) value of the rocking curve is 39.6″, and the piezoelectric coefficient d 11 value is 7.1 pC/N. The as-grown LTG crystal possesses excellent thermal properties, and the electrical resistivity at high temperatures (400∼600°C) was measured. After being heat-treated in Ar at 900, 1100, and 1300°C, the electrical resistivity increases evidently, and a La-rich and Ga-poor layer is observed on the surface of LTG. The LTG sample annealed in Ar at 1100°C for 10 h shows the highest electrical resistivity, which is up to 2.45*10 8 Ω⋅cm at 500°C. The content of oxygen vacancies of LTG increased after the annealing procedure, and the defect model was used to explain the increase in high-temperature electrical resistivity. The obtained high-quality large LTG crystal can be used in the field of high-temperature piezoelectric sensors. Graphical abstract: Image, graphical abstract